Evaluation of fliC-d based direct blood PCR assays for typhoid diagnosis. Issue 1 (December 2016) - Das, Surojit; Ray, Ujjwayini; Akhter, Irfaan; Chattopadhyay, Arka; Paul, Dilip; Dutta, Shanta
Abstract Background Typhoid cases need to be diagnosed accurately for early antibiotic therapy and reducing mortality. Identification ofSalmonella Typhi (S. Typhi) in blood culture is conclusive, but has poor sensitivity. Detection ofS. Typhi by PCR from blood sample has shown promise. Real-time quantitative PCR (Q-PCR) has been widely used in diagnostics for its rapidity and reliability. In the present study, the performance of molecular methods like conventional PCR (C-PCR), nested PCR (N-PCR) and Q-PCR were investigated and compared by targetingS . Typhi specific flagellarfliC-d gene directly in blood samples for typhoid diagnosis. Results Analytical sensitivities and specificities of the PCR assays were determined under laboratory condition followed by diagnostic performances were demonstrated in 110 clinically diagnosed typhoid fever (CDTF) cases included as study subjects. The DNA detection limit of C-PCR was observed 3 × 104 copies/reaction; those of N-PCR and Q-PCR (cutoff Ct value, ≤37) were 3 copies/reaction. The C-PCR was not further evaluated since it showed negative results with all clinical samples due to low sensitivity. Low isolation rate (21.8 %, 24/110) ofS . Typhi by blood culture did not reflect the true burden of typhoid fever among the study subjects. Hence diagnostic performances of N-PCR and Q-PCR were determined considering CDTF cases positive by any of the diagnostic assay methods (n  = 81) as true positives. Laboratory confirmed non-typhoidal cases (n  = 29) were included as true negatives. On comparison, although both the assays were 100 % specific; sensitivity (91.4 % vs. 81.5 %) and efficiency (93.6 % vs. 86.4 %) of Q-PCR were better, but statistically not significant (p  > 0.1) than N-PCR. The positive and negative likelihood ratios of Q-PCR were ∞ and 0.09 which indicated the potential clinical utility of Q-PCR for typhoid diagnosis. Q-PCR was more rapid than N-PCR (2 h vs. 6 h) in obtaining test results. Conclusions This study demonstrates for the first time that TaqMan-based Q-PCR assay performs more favorably than N-PCR for direct detection ofS. Typhi DNA in blood samples. Direct and quantitative blood Q-PCR is a rapid and reliable method for diagnosis of typhoid fever.